2018
DOI: 10.1002/2017je005503
|View full text |Cite
|
Sign up to set email alerts
|

Climate Forcing of Ripple Migration and Crest Alignment in the Last 400 kyr in Meridiani Planum, Mars

Abstract: The plains ripples of Meridiani Planum are the first paleo‐aeolian bedforms on Mars to have had their last migration episode constrained in time (to ~50–200 ka). Here we test how variations in orbital configuration, air pressure, and atmospheric dust loading over the past 400 kyr affect bedform mobility and crest alignment. Using the National Aeronautics and Space Administration Ames Mars Global Climate Model, we ran a series of sensitivity tests under a number of different conditions, seeking changes in wind … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 55 publications
(106 reference statements)
0
26
0
Order By: Relevance
“…Given the scale of the paleo‐dune field discussed in this work, and the consistency in preserved transport direction over >100 km, the ~90° difference between modern and ancient transport requires a regional‐scale difference in atmospheric conditions between today and ancient Mars at the time of this paleo‐dune field. Regional‐scale changes in the dominant sand‐transporting winds could be caused by changes in obliquity, atmospheric density, composition, or solar insolation (Fenton et al, ; Newman et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Given the scale of the paleo‐dune field discussed in this work, and the consistency in preserved transport direction over >100 km, the ~90° difference between modern and ancient transport requires a regional‐scale difference in atmospheric conditions between today and ancient Mars at the time of this paleo‐dune field. Regional‐scale changes in the dominant sand‐transporting winds could be caused by changes in obliquity, atmospheric density, composition, or solar insolation (Fenton et al, ; Newman et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…These boundary conditions can change over time and create shifting cryospheric and aeolian environments (e.g., Brothers & Kocurek, 2018). For example, studies have turned to variations in orbital parameters of Mars to explain climate change; Martian obliquity, which varies with a periodicity of 10 4 -10 5 years and which can strongly influence insolation and change atmospheric density and wind strengths (Brothers & Kocurek, 2018;Haberle et al, 2003;Head et al, 2003;Laskar et al, 2004), likely serves as a cyclical climate forcing agent influencing the formation and stabilization of dune fields and sand sheets (e.g., Ayoub et al, 2014;Brothers & Kocurek, 2018;Fenton et al, 2018;Laskar et al, 2004;. Since we can assume that these dune fields originally accumulated in an environment in which sand availability and wind transport capacity allowed sand saltation and dune accumulation, we can also interpret, in accordance with Fenton and Hayward (2010), the morphological shift to SI values >1 as a potential indicator of climate change postdating the formation of the dune fields.…”
Section: 1029/2018je005747mentioning
confidence: 99%
“…Thus, our combined observations of high-latitude dune mobility and modification may reflect a recent shift in the climate to activate or stabilize these dune fields. For example, studies have turned to variations in orbital parameters of Mars to explain climate change; Martian obliquity, which varies with a periodicity of 10 4 -10 5 years and which can strongly influence insolation and change atmospheric density and wind strengths (Brothers & Kocurek, 2018;Haberle et al, 2003;Head et al, 2003;Laskar et al, 2004), likely serves as a cyclical climate forcing agent influencing the formation and stabilization of dune fields and sand sheets (e.g., Ayoub et al, 2014;Brothers & Kocurek, 2018;Fenton et al, 2018;Laskar et al, 2004;.…”
Section: 1029/2018je005747mentioning
confidence: 99%
See 1 more Smart Citation
“…The orientation of the interior mound and trough is also consistent with mesoscale atmospheric modeling over Endeavour that shows a dominant wind regime with winds coming from the east to the southeast for multiple hours each sol (Chojnacki et al, ; Fenton et al, ). In addition, Fenton et al (, ) have shown that longer‐term regional‐scale easterlies are predicted to be the dominant sediment‐moving winds, consistent with the north‐south oriented crest lines associated with wind‐blown ripples that cover much of the Meridiani plains (Arvidson et al, ).…”
Section: Regional Contextmentioning
confidence: 82%